اسهام برامج التربية البدنية والرياضية في ارشاد وتوجيه سلوك المراهقين في المؤسسات التربوية - بزيو, سليم; عادل, بزيو; لزنك, أحمد (دفـاتر المـــــــــــخبـر, 2018)
الملخص: تلعب التربية البدنية والرياضية دورا هاما في تكوين شخصية الانسان ويرجع ذلك في المقام الأول الى أوجه النشاط التي تتضمنها منهاجها ولذا تؤكد الدول على أهمية برنامج التربية البدنية الرياضية في مختلف الاطوار التعليمية ودورها في تنمية وتطوير شخصية الطالب. لقد بينت الدراسات النفسية، أن النشاط البدنيالتربوي يلعب دورا بارزا في الصحة والتوافق النفسي كما أنه يعالج كثير من الانحرافات النفسية والسلوكية، كما يعتبر النشاط البدنيوالرياضي مجال لتأكيد المراهق لذاته. وتعتبر مرحلة المراهقة منعطف كبير تظهر فيه الازمات النفسية المؤدية الى المشاكل والانحراف؛ ويمكن ملاحظة التغيرات التي تحدثها التربية الرياضية منخلال سلوك الطلبة الرياضي،مثل احترام القيم الخلقية في الرياضة وفي ممارستها وفي مناقشتها. Abstract : Physical and sports education plays an important role in the formation of the human personality. This is mainly due to the aspects of activity in its curriculum. Therefore, countries emphasize the importance of the physical education program in various educational stages and its role in the development of the personality of the student. Psychological studies have shown that physical activity plays a prominent role in health and psychological compatibility. It also addresses many psychological and behavioral deviations. Physical activity is also a field of self-assertion. Adolescence is a major turning point in which psychological crises lead to problems and delinquency. The changes made by physical education can be observed through the students' athletic behavior. If their athletic behavior is described as an educational behavior consistent with the values ​​of the religious community, "which emphasizes respect for the ethical values ​​of sport and its practice and discussion